PERTANGGUNGJAWABAN PERDATA BAGI KORBAN LUMPUR LAPINDO BERDASARKAN PERSPEKTIF UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Santosa, Komang Vira Oktaviani Kurnia; Yoga, I Gede Perdana (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 8 (2024), 2025)
The aim of this text is to update the current regulations concerning the civil liability of Lapindo mudflow victims, particularly under Law Number 6 of 2023 on Job Creation. The research methodology employed here is normative legal research, utilizing three main approaches: statutory-regulatory approach (statute approach), analytical approach, and case approach. The findings of this study indicate that under the current Job Creation Law, compensation for losses due to the Lapindo mudflow should be provided in full by companies carrying out exploration and exploitation of the natural gas area in Poran, Sidoarjo, despite the lack of certainty given by the central government. And also, the court's decision means that full responsibility will not be given because it is considered not an obligation but merely a moral responsibility. Key Words: Civil Liability, Lapindo Mud, Job Creation Law